Lean in : women, work, and the will to lead - Sandberg, Sheryl (Alfred A. Knopf, 2013)
In "Lean In", Sheryl Sandberg -- Facebook COO and one of "Fortune" magazine's most powerful women in business -- looks at what women can do to help themselves, and make the small changes in their life that can effect change on a more universal scale. She draws on her own experiences working in some of the world's most successful businesses, as well as academic research, to find practical answers to the problems facing women in the workplace.